Surgical Management of Persistent Hymen in a Marwari Filly - A Case Report - Arunkumar, Ramasamy; Balamurugan, Kandasamy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Persistent hymen is a rare congenital anomaly of the  female genital tract and an important cause of infertility  in domestic animals. The hymen is formed from the epithelial  lining of the paramesonephric ducts and the urogenital sinus  at the vestibulo vaginal junction. Normally, it appears as a  thin mucosal fold which regresses or ruptures spontaneously  during the first estrus or coitus. However, incomplete  canalization of the embryonic vaginal septum results in  persistence of this membrane as a partial or complete  transverse barrier (Roberts, 1986). Such persistence is  considered a form of segmental aplasia caused by embryonic  malunion of the paramesonephric ducts and the ectodermal  urogenital sinus, leaving incomplete communication  between the caudal vagina and the vestibule. The degree  of obstruction varies, ranging from a partially occluding  membrane to complete imperforation. Complete obliteration  of the vaginal canal prevents normal drainage of secretions,  resulting in their accumulation within the vagina, cervix,  and uterus. This leads to conditions such as mucovagina,  mucocervix, and mucometra (Parkinson, 2001). Once the  vagina becomes distended, affected animal may exhibit  discomfort, straining, and tenesmus. Reports of persistent  hymen are uncommon in domestic species. It has been  documented in cattle (Madhusudhan et al., 2016; Kumar et  al., 2017), buffaloes (Kumar et al., 2016), bitches (Kruger et al., 2025), and goats (Da Silva et al., 2025). The anomaly has also  been reported sporadically in camels, llamas, and alpacas  (Fowler, 2011) and even in human beings, where it is a well recognised cause of primary amenorrhea and pelvic pain (Lee  et al., 2019). Although rare in equines, persistent hymen can  interfere with normal reproductive tract function, predispose  to infection, and cause breeding difficulties. The present  case report describes the clinical presentation, diagnosis,  and successful surgical management of persistent hymen  in a Marwari filly.
Keywords: Caslick's Procedure; Equine; Persistent Hymen; communication